Experimental study on the shear‐slip characteristics of natural fractures in shale reservoirs. Issue 4 (11th March 2022) - Shi, Zhaolong; Chen, Junbin; Gong, Diguang; He, Shunan; Jiang, Xu; Sun, Chen; Fan, Lingyi
Abstract: The injection of high‐pressure fluid and the propagation of hydraulic fractures (HF) can impact the stress state of natural fractures (NF) in shale reservoirs, which will lead to shear slip in NF that are in a critical stress state. However, the NF mechanics response mechanism during hydraulic fracture (HF) approximation has not been well investigated, especially under triaxial stress and injection conditions. This work focuses on the NF shear‐slip characteristics during HF through experimental investigation. Each shale sample contains a single rough NF in the tests, and high‐pressure fluid is injected through a pre‐drilled hole at the top of the sample. Meanwhile, the deformation (axial deformation and radial deformation), axial stress, and injection pressure of the sample during the experiment were recorded in real‐time. The experimental results show that the NF will initiate in tension or shear mode during the HF approaching process, and the fracture will produce shear slip in both initiation modes. In addition, the deviator stress, confining pressure, hydraulic fracture approach angle, and fracture surface roughness all affect the degree of shear slip in natural fractures (NF). The results further reveal the mechanical response mechanism of NF during hydraulic fracturing and provide a reference for optimizing hydraulic fracturing process measures. Abstract : This work designs and conducts natural fracture shear‐slip experiments under hydraulic fracture approximation conditions. The mechanism of natural fracture mechanics response during hydraulic fracturing has been investigated through laboratory experiments. The experimental results show that the natural fracture will initiate in tension or shear mode during the hydraulic fracture approaching process, and the fracture will produce shear slip in both initiation modes. In addition, the deviator stress, confining pressure, hydraulic fracture approach angle, and fracture surface roughness all affect the degree of shear slip in natural fractures.